Risk of spontaneous abortion among Danish pharmacy assistants. - Schaumburg, Inger; Olsen, Jørn (Scandinavian Journal of Work, Environment & Health, 1990)
A national study of the risk of medically verified spontaneous abortion was conducted among all pharmacy assistants in Denmark. The cohort was defined as 4939 female members of the Association of Danish Pharmacy Technicians between 1979 and 1984, all under the age of 40 years. Data on spontaneous and induced abortions, and births as well, were obtained from the national registers from the same time period. Data on work history and exposure to pharmaceuticals and chemicals were collected from self-administered postal questionnaires in April 1985 with a response rate of 93%. Studies of spontaneous abortion give rise to many methodological problems. In this study data were analyzed in a case-referent model using pharmacy assistants in administration and at the counter as the reference group. Generally, pharmacy assistants are at low risk with respect to spontaneous abortion. However, a few statistically significant results were found, but a decision on their importance must await further research.